IMPLEMENTASI MEDIA PEMBELAJARAN OPOS UNTUK MENINGKATKAN HASIL BELAJAR TEKNOLOGI INFORMASI DAN KOMUNIKASI KELAS X IIS SMA NEGERI 7 BULUKUMBA - Ahmad A (LPPM Universitas Muhammadiyah Bulukumba, 2022)
Abstract: Classroom action research is caused by the low quality of information and communication technology guidance results. This is due to the absence of ICT subjects in the structure of the school curriculum that causes students' treatment of ICT subjects to be considered unimportant. The method used is Class Action Research, Kemmis and McTaggart model A cycle-shaped procedure that will take place through two cycles, each cycle consisting of four stages: planning, execution, observation and reflection. The data collection technique used is a test in the form of questionnaires and non-tests in the form of observation of student activities. The study was conducted in class X IIS Sma Negeri 7 Bulukumba from June to December 2021. Research aims to improve the learning outcomes of ICT guidance. The results of the study is implementing OPOS learning media on ICT guidance increased, the average grade of first cycle student learning outcomes by 53.49 percent to 70.30 percent in second cycle. OPOS learning media also increased learning activity, in fist cycle student activity 65.33 percentincreased to 73.33 percent second cycle.